Long-term follow-up results of the SMART coil in the endovascular treatment of intracranial aneurysms. Issue 2 (April 2021) - McAvoy, Malia B; Cappuzzo, Justin M; Stapleton, Christopher J; Koch, Matthew J; Raymond, Scott B; Torok, Collin M; Patel, Aman B
Background: The Penumbra SMART coil is a novel device that becomes progressively softer from its distal to proximal end to maximize coil packing and prevent microcatheter prolapse or coil migration. Here, we report a large series of patients detailing the long-term experience of a single institution using the SMART coil among patients with intracranial aneurysms (IAs). Methods: Prospective data of 105 consecutive patients with 106 IAs treated using SMART coils was collected between March 2015 and July 2018. Clinical and angiographic data were analyzed. Results: Forty-nine patients (46.7%) presented with subarachnoid hemorrhage and 16 (14.2%) had recurrent aneurysms. Two patients had minor intraprocedural ruptures and remained neurologically stable. One patient had a thromboembolic complication with progressive neurologic decline. There was only one case microcatheter prolapse related to placement of a stent before coiling. An initial post-treatment modified Raymond-Roy Occlusion Classification (mRROC) I or II closure was achieved in 56 (52.8%) aneurysms. The average time to last follow-up was 8.4 months at which 70 (81.4%) aneurysms had mRROC I or II occlusion and a major recurrence was seen in 5 (5.8%) patients. Thirteen (12.3%) aneurysms required re-treatment of which one aneurysm was clipped. Conclusions: The Penumbra SMART coil is safe and effective for the endovascular treatment of appropriately selected IAs. Additional studies at multiple centers comparing safety and efficacy profile over long-term periods to other mainstream coils are necessary.